Literature Review : Gambaran Tindakan Perawat Mengatasi Nyeri Pasien Post Operasi Laparatomi Di Rumah Sakit - mulia hakam; Kushariyadi Kushariyadi; Noviana Intan Putri Chayaning Pribadi (Poltekkes Kemenkes Mataram, 2024)
Introduction:the pain of post-operative laparotomy is caused by tissue discontinuity or surgical wounds due to surgical incisions, so the skin's nerve cells become damaged. Laparotomy pain is often found in severe and moderate levels of pain intensity due to damage to the integument, muscle tissue, and vessels, and it causes in longer pain during the recovery period. Purpose: describe the actions of nurses in dealing with the pain of post-operative laparotomy patients in the hospital. Methods: this literature review uses the Google Scholar, PubMed, and Science Direct databases with cohort study designs, cross-sectional studies, case studies, randomized control trial studies, quasi-experimental studies published between 2019-2023. Result: the 10 articles reviewed in this study showed that the pain felt by post-operative laparotomy patients in the hospital experienced a decrease in the pain scale, from moderate pain to mild pain. Nursing actions related to pain can be done with pharmacological and non-pharmacological approaches. Analysis:the pharmacological approach can be carried out by administering analgesic therapy to reduce the intensity of pain felt by the patient while the non-pharmacological approach can be carried out by providing therapy such as; murottal Al-Qur'an therapy, lemon aromatherapy, deep breathing relaxation, finger grip relaxation, and hand massage therapy. Discussion: Pharmacological and non-pharmacological nursing actions carried out can reduce the pain scale of post-operative laparotomy patients in hospital from moderate to mild Keywords: pain, post-operative laparotomy, nurse actions